5-year efficacy and safety of secukinumab in patients with ankylosing spondylitis: end-of-study results from the phase 3 MEASURE 2 trial. (June 2020) - Marzo-Ortega, Helena; Sieper, Joachim; Kivitz, Alan J; Blanco, Ricardo; Cohen, Martin; Pavelka, Karel; Delicha, Eumorphia M; Stefanska, Anna; Richards, Hanno B; Rohrer, Susanne
Summary: Background: Secukinumab, a fully human monoclonal antibody that directly inhibits interleukin 17A, has shown significant and sustained improvement in the signs and symptoms of ankylosing spondylitis over 3 years in the MEASURE 2 study. We report the 5-year (end-of-study) results of subcutaneous secukinumab 150 mg in the MEASURE 2 study. Methods: MEASURE 2 was a phase 3, double-blind, randomised, placebo-controlled, study done in 13 countries and 53 centres. Patients with ankylosing spondylitis who were 18 years of age or older and fulfilled the modified New York criteria were randomly assigned to receive secukinumab (150 mg or 75 mg) or placebo subcutaneously at baseline and weeks 1, 2, and 3, and then every 4 weeks from week 4. At week 16, patients initially given placebo were randomly assigned again (placebo switchers) to receive secukinumab 150 mg or 75 mg. Efficacy results are reported for patients initially randomised to secukinumab 150 mg and those who switched from placebo to secukinumab 150 mg at week 16. An optional dose escalation from secukinumab 75 mg to 150 mg was initiated beginning week 140. We assessed efficacy endpoints at week 260 (5 years), including Assessment of Spondyloarthritis International Society (ASAS) 20 and ASAS 40, inactive disease according to ankylosing spondylitis disease activity score with C-reactive protein (ASDAS-CRP), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), BASDAI50, Bath Ankylosing Spondylitis Metrology Index, Bath Ankylosing Spondylitis Functional Index, Short Form-36 Physical Component Summary, and ASAS partial remission. Analyses were stratified by anti-tumour necrosis factor (TNF) status (anti-TNF-naive and anti-TNF inadequate response). The safety analysis included all patients who received one dose or more of secukinumab. We report data as observed without accounting for missing data. The MEASURE 2 study was registered with ClinicalTrials.gov, NCT01649375 . Findings: 219 patients were randomly assigned during the trial and 150 (68%) completed 5 years of treatment, including 82 (77%) of 106 patients in the secukinumab 150 mg group and 68 (65%) of 105 in the secukinumab 75 mg group. Efficacy analysis in the secukinumab 150 mg group included 53 patients who completed the study and one additional patient who was assessed in the treatment period weeks 212–260, but did not complete the study. 134 (61%) of 219 patients were anti-TNF-naive and 85 (39%) were anti-TNF inadequate responders. ASAS responses at 5 years with secukinumab 150 mg were 36 (67%) of 54 patients (ASA20) and 27 (50%) patients (ASAS40). Sustained improvement was observed across other efficacy endpoints with secukinumab 150 mg at 5 years. At 5 years, the proportion of patients achieving efficacy endpoints of BASDAI 50 response was 53% (44/83); ASAS 5/6 response was 51% (42/83); ASDAS-CRP inactive disease was 21% (17/81); and ASAS partial remission was 25% (21/83). Exposure-adjusted incidence rates with any secukinumab dose for selected adverse events were 1·0 per 100 patient-years (95% CI 0·4–1·9) for Candida infections, 0·5 (0·1–1·2) for Crohn's disease, 0·4 (0·1–1·1) for ulcerative colitis, 0·6 (0·2–1·4) for major adverse cardiovascular events, 0·5 (0·1–1·2) for uveitis, and 0·6 (0·2–1·4) for malignant or unspecified tumours. Interpretation: Secukinumab 150 mg provided sustained improvement in the signs, symptoms, and physical function in patients with ankylosing spondylitis after 5 years of treatment. The safety profile of secukinumab remained consistent with previous reports. Funding: Novartis Pharma.